Increases in Serious Psychological Distress among Ontario Students between 2013 and 2017: Assessing the Impact of Time Spent on Social Media. (August 2021) - Cook, Steven; Hamilton, Hayley A.; Montazer, Shirin; Sloan, Luke; Wickens, Christine M.; Cheung, Amy; Boak, Angela; Turner, Nigel E.; Mann, Robert E.
Objective: The objective of the current research was to examine the association between time spent on social media and serious psychological distress between 2013 and 2017, a period when the rates of both were trending upward. Methods: The current study analyzed population-based data from 3 waves of the Ontario Student Drug Use and Health Survey ( N = 15, 398). Multivariate logistic regression models were used to examine the association between time spent on social media and serious psychological distress controlling for theoretically relevant covariates. Interactions were tested to assess whether the association changed over time. Results: The prevalence of serious psychological distress increased from 10.9% in 2013 to 16.8% in 2017 concomitantly with substantial increases in social media usage, especially at the highest levels. In the multivariate context, we found a significant interaction between social media use and the survey year which indicates that the association between time spent on social media and psychological distress has decreased from 2013 to 2017. Conclusion: Although both social media use and psychological distress increased between 2013 and 2017, the interaction between these variables indicates that the strength of this association has decreased over time. This finding suggests that the higher rate of heavy social media use in 2017 compared to 2013 is not actually associated with the higher rate of serious psychological distress during the same time period. From a diffusion of innovation perspective, it is possible that more recent adopters of social media may be less prone to psychological distress. More research is needed to understand the complex and evolving association between social media use and psychological distress. Researchers attempting to isolate the factors associated with the recent increases in psychological distress could benefit from broadening their investigation to factors beyond time spent on social media.